Innovative contracts, sound relationships : - Brocklehurst, Clarissa (World Bank, 2004)
In 1995, the Government of Senegal launched wide-reaching reforms in the urban water sector. The reforms consisted of dissolving the state-run water company and creating a new asset-holding company that owned all the fixed assets in the government's name and had a mandate to manage the sector. The distribution and production was delegated to a separate entity, and a private operator was engaged to run the system. Eight years later, these reforms have resulted in significantly better services and financial health for the sector. There has been a 20 percent increase in the amount of water supplied, and the number of customers connected has increased by 35 percent.